Leptospiral flagellar sheath protein FcpA interacts with FlaA2 and FlaB1 in Leptospira biflexa - Sasaki, Yuya; Kawamoto, Akihiro; Tahara, Hajime; Kasuga, Kie; Sato, Ryoichi; Ohnishi, Makoto; Nakamura, Shuichi; Koizumi, Nobuo (PLOS ONE, 2018)
Leptospira spp. are spirochete bacteria that possess periplasmic flagella (PFs) underneath the outer membrane; each flagellum is attached to each end of the protoplasmic cylinder. PFs of Leptospira have a coiled shape that bends the end of the cell body. However, the molecular mechanism by which multiple flagellar proteins organize to form the distinctively curled PF of Leptospira remains unclear. Here we obtained a slow-motility mutant of L. biflexa MD4-3 by random insertion mutagenesis using a Himar1 transposon. In MD4-3, the gene encoding the flagellar sheath protein, flagellar-coiling protein A (FcpA), which was recently identified in L. interrogans, was inactivated. As with L. interrogans ΔfcpA strains, the L. biflexa ΔfcpA strain lacked a distinct curvature at both ends of the cell body, and its motility was significantly reduced as compared with that of the wild-type strain. PFs isolated from the ΔfcpA strain were straight and were thinner than those isolated from the wild-type strain. Western blot analysis revealed that flagellar proteins FlaA1, FlaA2, FlaB1, and FlaB2 were expressed in the ΔfcpA strain but the flagellar proteins, except for FlaB2 were not incorporated in its PFs. Immunoprecipitation assay using anti-FcpA antiserum demonstrated that FcpA associates with FlaA2 and FlaB1. The association between FcpA and FlaA2 was also verified using pull-down assay. The regions of FlaA2 and FlaB1 interacting with FcpA were determined using a bacterial two-hybrid assay. These results suggest that FcpA together with FlaA2, produces coiling of PF of the Leptospira, and the interaction between the sheath and core filament may be mediated by FcpA and FlaB1.